KONTRIBUSI KITAB TA'WIL MUKHTALAF AL-HADITH TERHADAP RESOLUSI KONFLIK DALAM PEMAHAMAN KEAGAMAAN - Akib, Moh; Muttaqin, Khairul (Jurnal Ushuluddin, 2025)
AbstractThe book Ta'wil Mukhtalaf al-Hadith by Ibn Qutaybah al-Dinawari represents a significant effort to resolve apparent contradictions in hadith texts. This article aims to examine the book's contribution to conflict resolution in religious understanding, specifically how it serves as a guide for critically and moderately understanding differences in hadith. This study employs content analysis of the Ta'wil Mukhtalaf al-Hadith text, combined with a historical-critical approach to explore the context of the book's composition and its impact on the tradition of hadith interpretation. The findings reveal that Ibn Qutaybah successfully offers a comprehensive interpretive framework, emphasizing the importance of understanding the asbabul wurud (circumstances of the hadith's narration) and employing reason in interpreting texts. This approach not only resolves apparent contradictions but also encourages readers to integrate a holistic understanding of the text. The study concludes that Ta'wil Mukhtalaf al-Hadith significantly contributes to fostering an inclusive religious understanding and avoiding polarization caused by narrow interpretations.Abstrak.Kitab Ta'wil Mukhtalaf al-Hadith karya Ibn Qutaybah al-Dinawari merupakan salah satu upaya signifikan dalam menyelesaikan kontradiksi yang tampak dalam teks-teks hadis. Artikel ini bertujuan untuk mengkaji kontribusi kitab tersebut terhadap resolusi konflik dalam pemahaman keagamaan, khususnya bagaimana ia menjadi panduan untuk memahami perbedaan dalam hadis secara kritis dan moderat. Penelitian ini menggunakan metode analisis isi (content analysis) terhadap teks kitab Ta'wil Mukhtalaf al-Hadith, dengan pendekatan historis-kritis untuk menelaah konteks penulisan kitab tersebut serta dampaknya pada tradisi pemahaman hadis. Hasil penelitian menunjukkan bahwa Ibn Qutaybah berhasil menawarkan kerangk a interpretasi yang komprehensif, dengan menekankan pentingnya memahami konteks asbabul wurud (sebab-sebab hadis diucapkan) serta penggunaan akal dalam menafsirkan teks. Pendekatan ini tidak hanya menyelesaikan kontradiksi yang terlihat tetapi juga mendorong pembaca untuk mengintegrasikan pemahaman teks secara holistik. Artikel ini menyimpulkan bahwa Ta'wil Mukhtalaf al-Hadith memberikan kontribusi yang signifikan dalam membangun pemahaman keagamaan yang inklusif dan menghindari polarisasi akibat interpretasi yang terbatas.